A copper-chromium-zirconium alloy contact wire and a method for manufacturing the same

CN122957068APending Publication Date: 2026-10-23FUJIKURA HENGTONG AERIAL CABLE SYST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611319318.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0007]为解决上述技术问题,本发明提供了一种铜铬锆合金接触线及其制备方法,将固溶处理集成于连续挤压工序中,省去独立的离线固溶加热炉,实现“挤压固溶”一体化;固溶在连续挤压过程中完成,材料完成固溶的瞬间即被挤出并进入冷却阶段,不存在传统离线固溶工艺中坯料“从固溶炉到淬火槽”的转移间隔,从根源上消除大卷重线坯因“入水间隔长”引发的温度下降以及合金元素过早析出问题,同时单根线材连续生产模式下,在线冷却系统可直接高效均匀地冲击材料表面,有效打破易形成的蒸汽膜,实现快速均匀冷却,彻底解决大卷重坯料整体入水淬火时由蒸汽膜隔热造成的冷却不均难题,达成均匀、高效的固溶处理效果

Benefits of technology

(1)本发明所述的制备方法采用连续挤压在线固溶结合即时连续冷却的工艺模式,可使所得铜铬锆合金接触线在实现高强度与高导电率良好匹配的同时,完全满足铁路行业标准要求。该工艺利用连续挤压过程产生的摩擦热与塑性变形热完成固溶处理,从根源消除传统离线固溶工艺坯料转移带来的入水间隔,材料在挤压动态过程中完成固溶后即刻进入可控冷却环节,保障固溶组织的新鲜程度与整体一致性。依托单根线材连续生产的特点,在线冷却系统可高效破除材料表面蒸汽膜,实现快速均匀冷却,解决大卷重坯料整体淬火时蒸汽膜隔热造成的冷却不均难题,为制备组织均一、性能稳定的接触线提供保障。该在线固溶过程热量源自挤压腔体内部,热量传递直接均匀,规避外部加热带来的炉内温场不均问题;铸杆在塑性变形的同时完成合金元素固溶扩散,形成过饱和固溶体,挤压的剧烈变形还能够破碎铸坯晶粒,配合高温下溶质原子充分扩散,消减铸坯存在的成分偏析,得到晶粒细小、成分均匀的坯料组织,为后续冷加工及时效处理奠定组织基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122957068A_ABST
    Figure CN122957068A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of copper chromium zirconium alloy contact line and its preparation method, belong to contact line technical field.The present application is integrated in continuous extrusion process with solid solution treatment, independent offline solid solution heating furnace is saved, realizes " extrusion solid solution " integration;Solid solution is completed in continuous extrusion process, material is extruded and enters cooling stage immediately after completing solid solution, there is no " from solid solution furnace to quenching tank " transfer interval of blank in traditional offline solid solution process, temperature drop caused by " long interval into water " of large volume heavy line blank and alloy element early precipitation problem are eliminated fundamentally, while in single wire continuous production mode, online cooling system can directly efficiently and uniformly impact material surface, effectively break the steam film that is easy to form, realize fast and uniform cooling, thoroughly solve the uneven cooling problem caused by steam film heat insulation when large volume heavy blank is integrally water-quenched, reach uniform, efficient solid solution treatment effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of contact wire technology, and particularly relates to a copper-chromium-zirconium alloy contact wire and its preparation method. Background Technology

[0002] The core component of the electrified railway power supply system is the contact wire above the train. Through continuous contact with the train's pantograph, it ensures stable power transmission and is a crucial component for guaranteeing the safe and high-speed operation of high-speed railways. With the continuous increase in operating speeds of high-speed railways in China, the service conditions of the contact wire are becoming increasingly demanding, placing extremely high demands on the comprehensive performance of materials. It must possess ultra-high tensile strength to withstand high-frequency dynamic tension and impact loads during operation; excellent conductivity to ensure efficient transmission of high-power electricity; and good wear resistance and fatigue resistance to withstand complex conditions such as pantograph friction and train vibration over long periods, delaying material aging and failure. Among existing alloy material systems, copper-chromium-zirconium alloy combines excellent mechanical and electrical properties and is recognized in the industry as the third-generation high-speed railway contact wire material suitable for lines with speeds of 400 km / h and above.

[0003] According to railway industry standards, the alloy composition of copper-chromium-zirconium alloy contact wires is strictly limited. The mass fraction of chromium is 0.20wt%-1.0wt%, and the mass fraction of zirconium is 0.02wt%-0.20wt%, with the remainder being the copper matrix and trace amounts of unavoidable impurities. This composition system exhibits excellent performance adaptability. Chromium has extremely low solid solubility in the copper matrix, minimizing the negative impact of alloy solute atoms on the matrix's conductivity and ensuring efficient power transmission. The high melting point and excellent corrosion resistance of zirconium significantly improve the alloy's high-temperature service stability. Simultaneously, chromium and zirconium can form fine, dispersed precipitates within the copper matrix, effectively refining the alloy's grain structure and significantly improving the tensile strength and wear resistance of the contact wire, achieving synergistic optimization of conductivity and mechanical properties. However, due to the high reactivity, volatility, and easy oxidation of chromium and zirconium, the industrial continuous preparation of copper-chromium-zirconium alloys is extremely difficult. There are many problems such as coarse grains in the cast billet, hot cracking and billet breakage, and compositional segregation. Large-size continuous mass production and performance balance control have always been the core technical bottlenecks in the industry.

[0004] Currently, the industry generally employs a traditional multi-stage integrated process for manufacturing copper-chromium-zirconium alloy contact wires. First, the smelted alloy raw materials are continuously cast into a continuous rod, which is then extruded and sized. The rod is then fed into an independent heating furnace and held at 900-1000℃ for an extended period to allow chromium and zirconium to fully dissolve and form a supersaturated solid solution. This solution is then rapidly cooled in water to lock in the solid solution structure. Subsequently, the rod blank is processed to near-finished dimensions through multiple cold working passes, followed by aging treatment at 400-500℃ to allow alloying elements to precipitate as dispersed strengthening phases. Finally, it is precision drawn into a finished contact wire with a uniquely shaped grooved structure. While this process allows for large-scale production of alloy contact wires, it has significant technical limitations in large-coil heavy industrial production, making it difficult to meet the high-quality production demands of high-end high-speed rail contact wires.

[0005] The shortcomings of traditional manufacturing processes are concentrated in multiple dimensions, including production quality, efficiency, and cost. Firstly, offline solution treatment is energy-intensive and has poor performance consistency. Independent high-temperature heating and quenching processes are extremely energy-intensive, and during the high-temperature transfer of large, heavy billets, elements are prone to premature precipitation, disrupting the supersaturated solid solution structure. Simultaneously, the Leidenfrost effect easily occurs during the quenching stage, leading to uneven cooling of the billet and fluctuations in the mechanical and electrical properties along the length of the finished product, resulting in insufficient quality stability. Secondly, finished product forming defects are frequent. Hard chromium and zirconium particles inside the alloy easily cause severe friction and localized heat accumulation during drawing, resulting in softening and sticking of the copper matrix, inducing surface scratches and internal microcracks. Furthermore, the narrow metal flow space and concentrated heat accumulation in irregularly shaped grooves easily lead to defects such as material accumulation, incomplete groove filling, and folded flash, significantly reducing the fatigue life and service safety of the contact line. Third, the production process is lengthy and the yield is low. In order to avoid forming defects, the deformation amount per pass needs to be reduced and the number of drawing passes and intermediate annealing processes need to be increased during production. This results in a long production cycle, high energy consumption, and low efficiency. The overall yield is only about 70%, and the production cost remains high, which seriously restricts the large-scale promotion and application of high-quality large-coil heavy copper-chromium-zirconium alloy contact wires.

[0006] Based on this, the present invention is proposed. Summary of the Invention

[0007] To address the aforementioned technical problems, this invention provides a copper-chromium-zirconium alloy contact wire and its preparation method, integrating solution treatment into a continuous extrusion process, eliminating the need for a separate offline solution heating furnace, and achieving "extrusion..." Integrated solution treatment: Solution treatment is completed during continuous extrusion. The material is extruded and enters the cooling stage the instant solution treatment is completed. There is no transfer interval between the billet and the quenching tank in the traditional offline solution treatment process. This eliminates the temperature drop and premature precipitation of alloying elements caused by the long water immersion interval of large coil billets. At the same time, in the continuous production mode of single wire rod, the online cooling system can directly, efficiently and uniformly impact the material surface, effectively break the easily formed vapor film, and achieve rapid and uniform cooling. This completely solves the problem of uneven cooling caused by the heat insulation of the vapor film when the large coil billet is immersed in water for quenching, and achieves a uniform and efficient solution treatment effect.

[0008] The first objective of this invention is to provide a method for preparing a copper-chromium-zirconium alloy contact wire, comprising the following steps: S1. Copper, copper-chromium master alloy and copper-zirconium master alloy are smelted and continuously cast to obtain cast rods; S2. The cast rod described in S1 is subjected to continuous extrusion, and the frictional heat and plastic deformation heat generated by continuous extrusion are used to achieve solution treatment, and the rod blank is obtained by cooling. S3. Roll or draw the rod blank described in S2 to obtain a wire blank; S4. The wire blank described in S3 is subjected to aging treatment and then cooled to obtain wire. S5. The wire described in S4 is rolled into shape to obtain the copper-chromium-zirconium alloy contact wire.

[0009] In one embodiment of the present invention, the mass fraction of chromium in the copper-chromium-zirconium alloy contact wire is 0.20%-1.00%, and the mass fraction of zirconium is 0.02%-0.20%.

[0010] In one embodiment of the present invention, in S1, the melting temperature is 1280°C-1350°C; And / or, the casting speed of the continuous casting is 550 mm / min-900 mm / min.

[0011] In one embodiment of the present invention, in S2, the diameter of the continuous extrusion roller is 580mm-630mm, and the speed of the extrusion roller is 4r / min-7r / min; the speed of the extrusion roller is set in combination with the diameter of the extrusion roller and other conditions to ensure that the die temperature is stably within the target solution range.

[0012] In one embodiment of the present invention, in S2, the solution treatment temperature is 900℃-1000℃; under this solution temperature condition, chromium and zirconium elements inside the alloy can be fully dissolved into the copper matrix, thereby forming a supersaturated solid solution.

[0013] In one embodiment of the present invention, in S2, the cooling rate is 130°C / s-150°C / s.

[0014] In one embodiment of the present invention, in S3, the total deformation of the rolling process is 45%-55%; The total deformation during drawing is 60%-68%.

[0015] In one embodiment of the present invention, in S4, the aging treatment temperature is 440℃-500℃ and the time is 2h-2.5h; the aging treatment promotes the precipitation of chromium and zirconium elements dissolved in the copper matrix in the form of fine dispersed phases, which has a significant strengthening effect on the matrix.

[0016] In one embodiment of the present invention, in S5, the rolling forming process involves 4-5 rolling passes. Rolling forming replaces traditional drawing, transforming the sliding friction between the material and the die into rolling friction, thus changing the contact state between the material and the die. This effectively reduces deformation heat and frictional resistance. The rolling deformation zone is dominated by compressive stress, which improves the material's plasticity. This allows the hard phase particles inside the alloy to be encapsulated by the copper matrix and achieve synergistic deformation, preventing the accumulation of hard phase particles on the die surface and solving the problem of die sticking caused by hard phases in copper-chromium-zirconium alloys. Simultaneously, the groove portion is precisely formed pass-by-pass using the roll pass pattern, resulting in uniform metal flow. This eliminates defects such as deformation heat concentration and material accumulation in the groove portion caused by sliding friction and hard phases in the drawing process, achieving full groove formation and significantly improving the forming quality and yield of the contact line.

[0017] A second objective of this invention is to provide a copper-chromium-zirconium alloy contact wire prepared by the method described above.

[0018] The technical solution of the present invention has the following advantages compared with the prior art: (1) The preparation method described in this invention adopts a process mode of continuous extrusion with online solution treatment combined with immediate continuous cooling, which enables the obtained copper-chromium-zirconium alloy contact wire to achieve a good match between high strength and high conductivity while fully meeting the requirements of railway industry standards. This process utilizes the frictional heat and plastic deformation heat generated during continuous extrusion to complete the solution treatment, eliminating the water entry interval caused by billet transfer in traditional offline solution treatment processes. After the material completes solution treatment during the dynamic extrusion process, it immediately enters the controllable cooling stage, ensuring the freshness and overall consistency of the solution structure. Relying on the characteristics of continuous production of single wire rods, the online cooling system can efficiently break the vapor film on the material surface, achieving rapid and uniform cooling, solving the problem of uneven cooling caused by vapor film insulation during the overall quenching of large coil heavy billets, and providing a guarantee for the preparation of contact wires with uniform structure and stable performance. The heat for this online solution treatment process originates from inside the extrusion chamber, ensuring direct and uniform heat transfer and avoiding the uneven temperature field issues caused by external heating. During plastic deformation, the casting rod undergoes solid solution diffusion of alloying elements, forming a supersaturated solid solution. The intense deformation during extrusion also breaks down the grains of the billet. Combined with the full diffusion of solute atoms at high temperatures, this reduces component segregation in the billet, resulting in a fine-grained, uniformly composed billet structure. This lays the structural foundation for subsequent cold working and aging treatment.

[0019] (2) The preparation method described in this invention uses rolling forming instead of the traditional drawing forming process to eliminate contact line groove forming defects and improve the surface quality of the finished product. This method transforms the sliding friction in the deformation process into rolling friction, reducing deformation resistance and deformation heat, and alleviating the problems of mold sticking and material accumulation caused by hard phase particles. The rolling deformation is dominated by compressive stress, and the stress field is uniformly distributed. The hard phase particles inside the alloy can deform in synergy with the copper matrix, avoiding various defects caused by local stress concentration. By controlling the forming step by step with the roll die, the metal flow in the groove is sufficient and the groove is fully filled. The overall surface of the finished contact line is smooth, which can avoid common problems in the drawing process such as folding, flash, and insufficient groove filling, ensuring uniform surface quality throughout the entire length of the wire, and at the same time, it can also achieve precise control of product dimensional accuracy.

[0020] (3) The preparation method described in this invention integrates the solution treatment process into the continuous extrusion process. It relies on the deformation heat of the material itself to reach the temperature required for solution treatment. It does not require a separate offline solution heating furnace or a long-term high-temperature heat preservation process, and has outstanding energy-saving and consumption-reducing advantages. The billet is continuously cast to obtain a dense cast rod, and then cold-worked by rolling or drawing. Cold working introduces a large number of dislocations into the material, which not only refines the structure and improves the strength of the matrix, but also provides nucleation sites for subsequent aging precipitation. Subsequent aging treatment promotes the precipitation of chromium and zirconium elements into dispersed nano-reinforcing phases in the supersaturated solid solution. The precipitated phases pin the dislocations to achieve material strengthening. At the same time, the precipitation of solute elements from the matrix also reduces their adverse effects on conductivity. By relying on the synergy of cold working and aging treatment processes, the mechanical properties and conductivity of the contact wire are optimized. The product also has good wear resistance, fatigue resistance and high-temperature softening resistance, and is suitable for the harsh service conditions of high-speed railways.

[0021] (4) The preparation method described in this invention also has the advantages of improving yield, reducing production costs, and being easy to industrialize and promote. The compressive stress deformation conditions of rolling are adapted to the plastic deformation characteristics of copper-chromium-zirconium alloys containing hard phases, which can reduce surface damage and internal microcrack defects induced by sliding friction in the drawing process, while eliminating some intermediate annealing and multiple surface treatment processes, shortening the overall production cycle, effectively improving yield and reducing production costs. Attached Figure Description

[0022] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein: Figure 1 This is a photograph of the copper-chromium-zirconium alloy contact wire prepared in Example 1 of the present invention. Figure 2 This is a physical image of the copper-chromium-zirconium alloy contact wire prepared in Comparative Example 1 of the present invention. Detailed Implementation

[0023] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.

[0024] In this invention, unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0025] In this invention, unless otherwise stated, the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0026] In this invention, unless otherwise specified, the experimental methods used in the embodiments of this invention are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0027] Example 1 The copper-chromium-zirconium alloy contact wire and its preparation method in this embodiment specifically include the following steps: S1. Electrolytic copper, copper-chromium master alloy and copper-zirconium master alloy are put into a non-vacuum airtight melting furnace according to the composition ratio of 0.65wt% chromium and 0.07wt% zirconium. They are melted and stirred at 1300℃-1350℃. The resulting melt is transported to the holding casting furnace through a trough. Under non-vacuum conditions, it is continuously cast by an upward casting device at a casting speed of 900mm / min to obtain a casting rod with a diameter of 20mm. S2. The casting rod is fed into a continuous extrusion press with an extrusion roller diameter of 580mm. The speed of the extrusion roller is set to 6r / min. Relying on the frictional heat and plastic deformation heat generated by extrusion, the temperature of the billet at the extrusion die is kept stable at 920℃-950℃, which promotes the full dissolution of chromium and zirconium into the copper matrix to form a supersaturated solid solution. After the solid solution is completed, it is extruded from the extrusion die and then enters the cooling water tank for continuous and rapid cooling in the form of a single wire. The cooling rate is about 150℃ / s, and a rod billet with a diameter of 28mm is obtained. S3. The bar billet is rolled in multiple passes at room temperature, and the total deformation is controlled to be about 49% to obtain a wire billet with a diameter of 20 mm. S4. Place the wire blank in an aging furnace and keep it at 460℃ for 2.5 hours for aging treatment. After aging, air cool it to room temperature to obtain wire. S5. The wire rod is rolled into shape using a 5-pass roll mill to obtain a cross-sectional area of ​​150mm². 2 Copper-chromium-zirconium alloy contact wire.

[0028] Example 2 The copper-chromium-zirconium alloy contact wire and its preparation method in this embodiment specifically include the following steps: S1. Electrolytic copper, copper-chromium master alloy and copper-zirconium master alloy are put into a non-vacuum airtight melting furnace according to the composition ratio of 0.72wt% chromium and 0.09wt% zirconium. They are melted and stirred at 1280℃-1320℃. The resulting melt is transported to the holding casting furnace through a trough. Under non-vacuum conditions, it is continuously cast by an upward drawing continuous casting device at a casting speed of 550mm / min to obtain a casting rod with a diameter of 25mm. S2. The casting rod is fed into a continuous extrusion press with an extrusion roller diameter of 630mm. The speed of the extrusion roller is set to 5r / min. Relying on the frictional heat and plastic deformation heat generated by extrusion, the temperature of the billet at the extrusion die is kept stable at 930℃-960℃, which promotes the full dissolution of chromium and zirconium into the copper matrix to form a supersaturated solid solution. After the solid solution is completed, it is extruded from the extrusion die and then enters the cooling water tank for continuous and rapid cooling in the form of a single wire. The cooling rate is about 130℃ / s, resulting in a rod billet with a diameter of 30mm. S3. The rod blank is drawn at room temperature, and the total deformation is controlled to be about 64% to obtain a wire blank with a diameter of 18mm. S4. Place the wire blank in an aging furnace and keep it at 480℃ for 2 hours for aging treatment. After aging, air cool it to room temperature to obtain wire. S5. The wire rod is rolled into shape using a four-pass rolling mill to obtain a cross-sectional area of ​​150 mm². 2 Copper-chromium-zirconium alloy contact wire.

[0029] Comparative Example 1 The process is basically the same as in Example 1, except that in S2, the cast rod is fed into a continuous extrusion press for extrusion (without online solution treatment), and the resulting extruded billet is transferred to a solution furnace, held at 940°C for 2 hours, and then continuously and rapidly cooled to obtain the rod billet.

[0030] Comparative Example 2 The process is basically the same as in Example 1, except that in S5, rolling is replaced by drawing.

[0031] Comparative Example 3 The process is basically the same as in Example 1, except that in S2, the speed of the extrusion roller is set to 2 r / min. The temperature of the billet at the extrusion die is kept stable at 640°C by relying on the frictional heat and plastic deformation heat generated by extrusion.

[0032] Test Example 1 Physical images of the copper-chromium-zirconium alloy contact wires prepared in Example 1 and Comparative Example 1 are shown below. Figures 1-2 As shown. From Figures 1-2 As can be seen, the copper-chromium-zirconium alloy contact wire prepared in Example 1 has a smooth surface, full metal filling in the groove, and a complete and regular groove outline without defects such as folds, flash, or material accumulation. In contrast, the copper-chromium-zirconium alloy contact wire prepared in Comparative Example 1 shows obvious material accumulation at the mold opening in the groove, and the metal stacking and deformation in the groove are defects. These defects will impair the fatigue performance of the contact wire and are not conducive to long-term service of the circuit.

[0033] Test Example 2 The contact wires prepared in the examples and comparative examples were tested for mechanical and electrical properties.

[0034] (1) Tensile strength: The test was conducted in accordance with the standard GB / T 4909.3-2009 Bare wire test method Part 3: Tensile test. The gauge length was set to 250 mm, and the specimen was subjected to uniaxial tension at a rate of 20 mm / min until the specimen broke. The tensile strength of the specimen was calculated based on the tensile force value of the specimen. (2) Conductivity: The test was conducted in accordance with the standard GB / T 3048.2-2007 Electrical Performance Test Methods for Wires and Cables Part 2: Resistivity Test of Metallic Materials. The four-terminal measurement technology was adopted and a high-precision digital DC resistance tester was used for measurement. Before the measurement, the sample was placed in an environment with a temperature of about 20℃ and an air humidity of about 75% RH for 16 hours. The test results were converted into the conductivity under the condition of 20℃ according to the temperature coefficient of resistance. (3) Yield: First, accurately measure the total weight of the cast rods put into continuous production and record it as the initial total weight M0. Track the entire production process and remove unqualified products with surface scratches, incomplete groove filling, substandard performance, out-of-tolerance dimensions, and products whose length does not meet the requirements of railway application anchor sections. Then, count the total weight M1 of qualified contact wires that meet the railway industry standards. Calculate the yield according to the formula: Yield = (Total weight of qualified contact wires M1 ÷ Initial total weight of cast rods M0) × 100%. Table 1 shows the final measured results: Table 1

[0035] As shown in Table 1, the contact wire of the embodiment is superior overall in terms of tensile strength, conductivity, and yield. This indicates that by combining continuous extrusion with online solution treatment, the independent offline solution treatment process is eliminated, avoiding the drawbacks of uneven temperature and premature element precipitation caused by offline high-temperature treatment. Furthermore, the use of rolling forming instead of traditional drawing improves the problems of difficult deformation of hard points and large mold friction damage, reduces surface and groove forming defects, and achieves a synergistic improvement in mechanical properties, conductivity, and yield.

[0036] Comparing Example 1 and Comparative Example 1, it can be seen that Comparative Example 1, which uses a traditional offline solution treatment process, exhibits large fluctuations in product performance and a significantly lower yield. This is because offline solution treatment requires the transfer and transportation of the billet, during which alloying elements are prone to premature precipitation, making it difficult to stably maintain a supersaturated solution structure. At the same time, the quenching and cooling process has poor cooling uniformity, resulting in inconsistent microstructure and properties along the length of the product, making it more prone to defects during the forming stage and reducing the yield.

[0037] Comparing Example 1 and Comparative Example 2, it can be seen that although Comparative Example 2 can achieve similar tensile strength and conductivity, the yield rate is significantly reduced, and the products are more prone to surface damage defects. This is because drawing relies on sliding friction to complete deformation. Hard precipitates inside the alloy will aggravate frictional heat generation and die wear. Stress concentration at irregular groove locations can easily cause scratches and microcracks, resulting in a large number of scrapped products.

[0038] Comparing Example 1 and Comparative Example 3, it can be seen that in Comparative Example 3, due to the lower extrusion roller speed, the die temperature could not reach the effective solution treatment temperature, resulting in a significant decrease in both tensile strength and electrical conductivity. This indicates that only by matching a specific extrusion roller speed and relying on the heat of extrusion plastic deformation to raise the billet to a suitable temperature can chromium and zirconium alloy elements be fully dissolved into the copper matrix, achieving the technical effect of online solution treatment and ensuring the comprehensive material properties after subsequent aging.

[0039] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a copper-chromium-zirconium alloy contact wire, characterized in that, Includes the following steps: S1. Copper, copper-chromium master alloy and copper-zirconium master alloy are smelted and continuously cast to obtain cast rods; S2. The cast rod described in S1 is subjected to continuous extrusion, and the frictional heat and plastic deformation heat generated by continuous extrusion are used to achieve solution treatment, and the rod blank is obtained by cooling. S3. Roll or draw the rod blank described in S2 to obtain a wire blank; S4. The wire blank described in S3 is subjected to aging treatment and then cooled to obtain wire. S5. The wire described in S4 is rolled into shape to obtain the copper-chromium-zirconium alloy contact wire.

2. The method for preparing the copper-chromium-zirconium alloy contact wire according to claim 1, characterized in that, The copper-chromium-zirconium alloy contact wire contains 0.20%-1.00% chromium and 0.02%-0.20% zirconium by mass.

3. The method for preparing the copper-chromium-zirconium alloy contact wire according to claim 1, characterized in that, In S1, the melting temperature is 1280℃-1350℃; And / or, the casting speed of the continuous casting is 550 mm / min-900 mm / min.

4. The method for preparing the copper-chromium-zirconium alloy contact wire according to claim 1, characterized in that, In S2, the diameter of the continuous extrusion roller is 580mm-630mm, and the rotation speed of the extrusion roller is 4r / min-7r / min.

5. The method for preparing the copper-chromium-zirconium alloy contact wire according to claim 1, characterized in that, In S2, the solution treatment temperature is 900℃-1000℃.

6. The method for preparing the copper-chromium-zirconium alloy contact wire according to claim 1, characterized in that, In S2, the cooling rate is 130°C / s-150°C / s.

7. The method for preparing the copper-chromium-zirconium alloy contact wire according to claim 1, characterized in that, In S3, the total deformation of the rolling process is 45%-55%; The total deformation during drawing is 60%-68%.

8. The method for preparing the copper-chromium-zirconium alloy contact wire according to claim 1, characterized in that, In S4, the aging treatment temperature is 440℃-500℃ and the time is 2h-2.5h.

9. The method for preparing the copper-chromium-zirconium alloy contact wire according to claim 1, characterized in that, In S5, the rolling process for forming is 4-5 passes.

10. A copper-chromium-zirconium alloy contact wire prepared by any one of claims 1-9.